1998
DOI: 10.1002/(sici)1099-0488(19980415)36:5<763::aid-polb4>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Triple melting behavior of poly(ethylene terephthalateco-1,4-cyclohexylene dimethylene terephthalate) random copolyesters

Abstract: The melting behavior of poly(ethylene terephthalate co‐1,4‐cyclohexylene dimethylene terephthalate) [PET/CT] random copolyesters has been studied. The basis of this analysis was the triple melting behavior of PET homopolymers, which is commonly observed after a period of isothermal crystallization followed by linear heating in a differential scanning calorimeter. Both ET and CT homopolymers are able to crystallize, and as a consequence, the copolymer morphology depends on the ET/CT ratio. It has been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 3 publications
2
29
0
Order By: Relevance
“…Although the single component blends have almost the same melting peak temperature, an increase of the T m with increasing PEN levels can still be observed over the differently reacted materials. It was previously reported24, 25 that nonregularity in the polyester structure decreases the melting temperature and is the reason for a decrease in melting temperature with increasing residence time and concomitant transesterification. Differences in crystallizability of heterogeneous polymers is related to the existence of distributions of crystallizable sequences of different lengths 24.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the single component blends have almost the same melting peak temperature, an increase of the T m with increasing PEN levels can still be observed over the differently reacted materials. It was previously reported24, 25 that nonregularity in the polyester structure decreases the melting temperature and is the reason for a decrease in melting temperature with increasing residence time and concomitant transesterification. Differences in crystallizability of heterogeneous polymers is related to the existence of distributions of crystallizable sequences of different lengths 24.…”
Section: Resultsmentioning
confidence: 88%
“…Crystal imperfections, which can be related to the molecular structure, will lower the heat of fusion and melting temperatures and be exploited to fractionate the material. For instance, PET containing small amounts of 1,4‐cyclohexylene units as comonomer exhibits a direct correlation between the amplitude of the lower temperature melting peak with comonomer content 25. The fact that the PEN used for the blends is a copolymer containing 8 mol % PET units could explain why blends containing low PEN levels are more affected by changes in the transesterification than the blends of higher PEN concentrations (the PEN copolymer is initially highly transesterified).…”
Section: Resultsmentioning
confidence: 99%
“…Many investigations on the origin of the multiple melting behavior in semicrystalline polymers have been performed. [26][27][28][29] Various factors such as the change in morphology, orientation effects, the presence of more than one crystal modification, and meltingrecrystallization-remelting process occurring during DSC scans have influences on the multiple melting behaviors. In DSC thermograms of the annealed NT-7.5 shown in Figure 7, it was observed that with increasing annealing temperature within the annealing temperature range (140~200 o C), the lower melting peak shifted to higher temperatures, and the height ratio of the lower and higher melting peaks changed with annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…PET and PTT can be crystallized from the melt under a wide range of supercooling conditions, or they can be quenched into the amorphous state, and then the crystallization process can proceed through the heating of a specimen above the glass‐transition temperature ( T g ). Normally, PET and PTT exhibit multiple melting peaks during heating scanning with differential scanning calorimetry (DSC), regardless of whether crystallization occurs from the rubbery amorphous state or from the melt 14–21. The lowest melting peak, observed approximately 10 °C above the crystallization temperature ( T c ), has been attributed to the fusion of crystals grown during secondary crystallization.…”
Section: Introductionmentioning
confidence: 99%